Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41408-023-00820-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of early bone marrow MRD status in CAR-T therapy for myeloma

Abstract: Bone marrow (BM) assessment of minimal residual disease (MRD) is prognostic for survival in multiple myeloma (MM). BM is still hypocellular at month 1 post CAR-T, thus the value of MRD negative (MRDneg) status at this timepoint is unclear. We examined the impact of month 1 BM MRD status in MM patients who received CART at Mayo Clinic between 8/2016 and 6/2021. Among 60 patients, 78% were BM-MRDneg at month 1; and 85% (40/47) of these patients also had decreased to less than normal level of both involved and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Accordingly, the presence of extramedullary disease after infusion with ide-cel was associated with inferior PFS in patients achieving undetectable MRD. These results confirm and expand the recent observations in patients treated with CAR T cells at the Mayo Clinic ( 17 ). Furthermore, it could help explain the cases in which the achievement of a transient MRD-negative status was followed by disease progression without ever attaining CR.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, the presence of extramedullary disease after infusion with ide-cel was associated with inferior PFS in patients achieving undetectable MRD. These results confirm and expand the recent observations in patients treated with CAR T cells at the Mayo Clinic ( 17 ). Furthermore, it could help explain the cases in which the achievement of a transient MRD-negative status was followed by disease progression without ever attaining CR.…”
Section: Discussionsupporting
confidence: 91%
“…This was sustained at 6 and 12 months, favorable in comparison with previous studies . Although bone marrow may still be hypocellular at the early time point after CAR T therapy, Lin Y et al recently reported that bone marrow MRD negative at month 1, regardless of cellularity status in bone marrow, correlated with CR/sCR response and prolonged PFS …”
Section: Discussionmentioning
confidence: 89%
“…11 Although bone marrow may still be hypocellular at the early time point after CAR T therapy, Lin Y et al recently reported that bone marrow MRD negative at month 1, regardless of cellularity status in bone marrow, correlated with CR/sCR response and prolonged PFS. 12 GC012F also showed a favorable safety profile without dose-limiting toxic effects. Cytopenia was the most common grade 3 or higher AE exhibiting a rapid recovery, faster than in the cohort of patients with RRMM.…”
Section: Discussionmentioning
confidence: 89%
“…According to a previous study, early MRD positivity likely predicts impending clinical relapse. 25 In our phase I clinical trials of CAR-T-cell treatment of the seven RRMM patients, the overall response rate (ORR) was 85.7% (6/7), and included four patients with an sCR, one patient with a CR, one patient with a PR and one patient with SD. Durable responses were found in four patients at the time of last follow-up, and disease relapse was detected in one patient at 19.2 months (figure 6G).…”
Section: Pd-1 Kd Bcma Car-t Cells Exhibited Comparable Tolerability A...mentioning
confidence: 99%